2014
DOI: 10.1103/physrevb.89.220201
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of many-body localization

Abstract: Following the field theoretic approach of Basko et al., Ann. Phys. 321, 1126(2006, we study in detail the real-time dynamics of a system expected to exhibit many-body localization. In particular, for time scales inaccessible to exact methods, we demonstrate that within the second-Born approximation that the temporal decay of the density-density correlation function is non-exponential and is consistent with a finite value for t → ∞, as expected in a non-ergodic state. This behavior persists over a wide range of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…In this region, the volume occupied by a typical wavefunction scales as anomalous power, D, of the full Hilbert space volume that continuously changes from D = 0 in the insulator to D = 1 in a fully delocalized state. In a qualitative agreement several groups have found that the dynamics in this region is often described by non-trivial power laws that are neither diffusive nor localized [6][7][8][9].…”
Section: Introductionsupporting
confidence: 55%
“…In this region, the volume occupied by a typical wavefunction scales as anomalous power, D, of the full Hilbert space volume that continuously changes from D = 0 in the insulator to D = 1 in a fully delocalized state. In a qualitative agreement several groups have found that the dynamics in this region is often described by non-trivial power laws that are neither diffusive nor localized [6][7][8][9].…”
Section: Introductionsupporting
confidence: 55%
“…Grover [22] showed that the eigenstates at this critical point have volume-law entanglement of small subsystems. Recent numerical work, which focused on the vicinity of the transition, has identified and explored the subdiffusive regime in the vicinity of the transition [17,23]. Finally, a very recent work explores a different RG approach to the MBL transition based on an assumed hierarchical structure of the relevant many-body resonances, arriving at similar conclusions to ours [24].…”
Section: Introductionmentioning
confidence: 83%
“…In the thermodynamic limit of infinite system this parameter is defined as the local spin-spin correlation function (29) taken in the infinite time limit [43] and averaged over the system eigenstates having zero energy. The latter choices correspond to the infinite temperature thermodynamic limit [27,28]. In that limit the average ergodicity parameter should approach zero in the delocalized state where correlations are subject to decay, while in the localized state it should be finite (unity in an infinitely strong disorder limit).…”
Section: Finite Size Scaling For Xy Modelmentioning
confidence: 99%
“…[26]). We consider the infinite temperature limit similarly to the previous work [27,28] because it is more convenient for analytical and numerical considerations while its generalization to the finite non-zero temperature is straightforward [29].…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation